Fence. Volume seven, Challengers - Pacat, C. S.; Pacat, C. S.; Johanna the Mad (BOOM! Box, 2025)
Kings Row are heading into the State Championships as underdog champions, and now have to contend with the best of the best in fencing-including potentially facing Exton themselves. Before they can get there though, they'll have to get through some of the other top teams, including some old rivals...